2007
DOI: 10.1002/ijc.23092
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) genotype distribution in invasive cervical cancers in France: EDITH study

Abstract: Invasive cervical cancer (ICC) remains a significant cause of morbidity and mortality in France. Since human papillomavirus (HPV) is the necessary cause of ICC, the aim of this study was to assess the type-specific prevalence of HPV in ICC in France in order to locally evaluate the potential benefit of an HPV 16/18 L1 virus-like particles (VLP) vaccination. A total of 516 histological specimens collected in 15 centers were analyzed. Among them, 86% had a diagnosis of squamous cell carcinoma (SCC) whereas 14% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0
18

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 24 publications
7
40
0
18
Order By: Relevance
“…Consequently, in a context of high Pap test coverage, lesions undetected by screening controls are more likely to be HPV16 or HPV18. This interpretation is consistent with the observation that the proportion of HPV16/18 in cancers is higher in high-income countries [Western Europe (45) and North America] with large diffusion of the Pap test and lower in low/middle-and lowincome countries (South America, Asia, and Africa; ref. 13).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, in a context of high Pap test coverage, lesions undetected by screening controls are more likely to be HPV16 or HPV18. This interpretation is consistent with the observation that the proportion of HPV16/18 in cancers is higher in high-income countries [Western Europe (45) and North America] with large diffusion of the Pap test and lower in low/middle-and lowincome countries (South America, Asia, and Africa; ref. 13).…”
Section: Discussionsupporting
confidence: 91%
“…GP5+/GP6+ primers amplify a broad spectrum of HPV genotypes by targeting a 150-bp fragment within the L1 open reading frame of the HPV genome (31). All samples and controls, independent of gel results, were subjected to the reverse line blot (RLB) for detection of 12 high-risk HPV types (16,18,31,33,35,39,45, 51, 52, 56, 58, and 59), 1 probably carcinogenic HPV type (68), and 5 possibly carcinogenic HPV types (26, 53, 66, 73, and 82; ref. 32).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Based on our results, we propose that among HR-HPV infected women, those with an HPV16 load of above 22,000 copies/10 3 cells or with an E2/E6 ratio below 0.5 are likely to present a high-grade lesion. These cutoff values, however, are relevant for HPV16 only, which is detected for 34 to 52% of patients with CIN2/3 and for 52 to 58% of cancers (4, 10, 34, 48) (62% of CIN2/3 and in 73% of cancers in France [42,43]). Because other HR-HPVs (e.g., HPV18, HPV31, and HPV45) are also responsible for cervical lesions, relevant cutoffs should be determined for these genotypes.…”
Section: Discussionmentioning
confidence: 97%
“…26,27 The IARC pooled analysis of 3085 invasive cervical carcinomas revealed that the five most common HPV genotypes were, in descending order of frequency, HPV16, 18, 45, 31, and 33. 10 In our study, these genotypes were detected in 74% of the cases.…”
Section: Discussionmentioning
confidence: 99%